Development of geoinformation system for identification and time monitoring of damaged lands due to illegal extraction of amber - Yanchuk, Oleksandr; Dets, Tetiana; Dmytriv, Olha; Ostapchuk, Serhii; Prokopchuk, Andrii; Trokhymets, Serhii; Yanchuk, Ruslan (Geodesy and Cartography, 2020)
On basis of the analysis of existing elaborations determining places of the illegal extraction of amber by data of remote sensing of the Earth were established basic deciphering signs of the phenomenon researched. Methods were developed to identify lands damaged as a result of the illegal extraction of amber taking into account the specifics of data processing obtained from different types of satellite surveying systems: WorldView-2/3, Pleiades-1, Spot-6/7, Planet Scope, Sentinel-2B. The structure is substantiated and modular geoinformation system was developed on basis of GIS QGIS with added modules from open libraries GDAL, GRASS. The developed methods and modules of geoinformation system were tested on researched testing grounds with automated identification and calculation of areas of damaged lands.